Migraine triggers and habituation of visual evoked potentials. (April 2018) - Lisicki, Marco; Ruiz-Romagnoli, Emiliano; Piedrabuena, Raúl; Giobellina, Roberto; Schoenen, Jean; Magis, Delphine
Background: Identifying specific subsets of patients within the clinical spectrum of migraine could help in personalizing migraine treatment. Profiling patients by combining clinical characteristics and neurophysiological biomarkers is largely unexplored. We studied the association between migraine attack triggers and habituation of visual evoked potentials. Methods: We personally interviewed 25 patients about their migraine triggers following a structured list, and measured the N1-P1 habituation slope over six blocks of 100 averaged pattern-reversal VEP afterwards. Results: The mean number of triggers per patient was 4.52 ± 1.42. Habituation slopes differed significantly between subjects who reported stress as a migraine trigger (deficient VEP habituation) and subjects who did not (preserved VEP habituation). For the remaining categories, the mean amplitude slope was always positive, indicating deficient habituation, and was not significantly different between subgroups. Conclusions: Migraine patients not reporting perceived stress as a trigger for their attacks might constitute a distinct clinic-physiological subset within the migraine spectrum.